IMPLEMENTASI MANAJEMEN KOLEKSI BAHAN PUSTAKA BAGI WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KLAS IIA YOGYAKARTA (BERDASARKAN GUIDELINES FOR LIBRARY SERVICE TO PRISONERS OLEH IFLA) - Agustian Bhaskoro Abimana Aryasatya (Central Library of Universitas Sebelas Maret, 2017)
The topic discussed in this research is how is the implementation of the collection management of library material for inmates in correctional facility level IIA of Wirogunan Yogyakarta (Based on Guidelines for Library Service to Prisoners by IFLA). The research employs descriptive-qualitative approach. Researchers will investigate and explain the facts narratively to be further described as they have been found in the field. Researchers will describe the results with comparator indicators that use the standard collection management for prisoners. The research end to the conclusion that the implementation of the collection management of library material for inmates in corectional facility level IIA Wirogunan Yogyakarta (Based on Guidelines for Library Service to Prisoners by IFLA)is already establised, but still many not yet according to standard which writer make as indicator. Lack of facilities that fit the ergonomics, still not according to the needs of the user, the collection of the number is still lacking, and staff who are far from expectations because it is not from a professional librarian.